Strategi Kelompok Tani Padi Dalam Implementasi Teknologi Pertanian di Lembang Kepe Tinoring Kecamatan Mengkendek Kabupaten Toraja - Elviani Randanan; Musdalifa Mahmud; Helda Ibrahim; Herman Nursaman (Jurnal MeA (Media Agribisnis), 2026)
Farmer groups are a forum for farmers to obtain non-formal education and obtain facilities from the government that can support the rice farming activities carried out, such as farmers are given training, insight into market access, obtain subsidized fertilizer, seeds, tools and agricultural machinery. This study aims to analyze the strategic role of farmer groups in the implementation of agricultural technology in rice farming. This study uses a qualitative analysis method, namely a method of in-depth data processing with data from observations, interviews and literature. The technique of analyzing qualitative data by summarizing categorizing and interpreting. Qualitative analysis is an analysis method using interviews and observations by answering questions such as what, why or how. The results of this study are in the form of technology implementation in rice farming cultivation which is implemented by 72.24% which means that in carrying out rice farming activities, farmers have utilized agricultural technology to facilitate in carrying out farming activities and reduce production process costs. Farmer groups as a forum for farmers to obtain non-formal education, a place for farmers to solve problems and express their opinions about what is found in the field related to their rice farming. Therefore, the government and extension workers should be more active in providing training and education to farmers so that they can broaden their horizons to current developments, thus enabling them to accept and embrace change in managing their farming businesses more effectively and efficiently.